PENGARUH GOOD GOVERNANCE, DESENTRALISASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA ORGANISASI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATING (Studi pada Organisasi Perangkat Daerah Kota Pekanbaru) - Riza Pramita Anugerah (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
Pekanbaru City Government Performance Report (LKj-IP) in 2016 received a Cscore (somewhat less) besides that there were still many Pekanbaru CityGovernment activities programs that did not reach the target with a small realizationpercentage of 50%. The purpose of this study was to examine the effect of goodgovernance, decentralization, and organizational commitment on organizationalperformance with organizational culture as a moderating variable in OPDPekanbaru. The population in this study was Pekanbaru Regional Organization(OPD), which amounted to 43 OPD. Respondents in this study were structuralofficials consisting of Echelon II, III, and IV in the OPD of Pekanbaru City. By usingthe purposive sampling method obtained a sample of 129 respondents. The datasource in this study is primary data. The data collection method used is the surveymethod using a questionnaire. Data analysis used Moderated Regression Analysis.The results of the study show that good governance, decentralization, andorganizational commitment have a partial effect on organizational performance,organizational culture strengthens the influence of good governance onorganizational performance, organizational culture reinforces the influence oforganizational commitment on organizational performance. But organizationalculture is not able to moderate the influence of decentralization on organizationalperformance.